Large bowel perforation secondary to CMV colitis: an unusual primary presentation of HIV infection. (21st December 2016) - Barling, Daniel Richard; Tucker, Simon; Varia, Haren; Isaacs, Peter
Abstract : We report a case of HIV-associated Cytomegalovirus colitis complicated by large bowel perforation. A 62-year-old man of same-sex relationship was not known to have HIV, but a diagnosis of inflammatory bowel disease was made early in his admission, with steroid treatment initiated. He was later confirmed to be HIV positive, and found to have multiple microperforations of the bowel necessitating ileocecectomy and Hartmann's procedures.